2016
DOI: 10.18632/aging.100874
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics profiling reveals novel markers for leukocyte telomere length

Abstract: Leukocyte telomere length (LTL) is considered one of the most predictive markers of biological aging. The aim of this study was to identify novel pathways regulating LTL using a metabolomics approach. To this end, we tested associations between 280 blood metabolites and LTL in 3511 females from TwinsUK and replicated our results in the KORA cohort. We furthermore tested significant metabolites for associations with several aging-related phenotypes, gene expression markers and epigenetic markers to investigate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 52 publications
2
39
0
Order By: Relevance
“…Another limitation of the present study was that the telomere length was determined in peripheral blood leukocytes, but not in the liver. However, recent study by Zierer et al 24 suggested that certain metabolites associated with aging and liver function, such as gamma glutamyl amino acids, are correlated with leukocyte telomere length. Our sample size was relatively small.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation of the present study was that the telomere length was determined in peripheral blood leukocytes, but not in the liver. However, recent study by Zierer et al 24 suggested that certain metabolites associated with aging and liver function, such as gamma glutamyl amino acids, are correlated with leukocyte telomere length. Our sample size was relatively small.…”
Section: Discussionmentioning
confidence: 99%
“…It is however not clear to which extent γ‐glutamyl dipeptides are suitable PEPT1 transport substrates. Yet, a variety of γ‐glutamyl‐peptides have been identified recently in biomarker discovery studies, and some of these peptides can be associated with diseases . We here show that uptake from the intestine from dietary sources contributes to the plasma level of these dipeptides.…”
Section: Discussionmentioning
confidence: 60%
“…We posit that sleep restriction/deprivation leads to a metabolic setting that could resemble aging and may serve as lead to understand the connection of sleep loss and incident neurodegenerative disorders. Comparison of some recent aging metabolomics studies [47][48][49][50][51][52] and sleep metabolomics studies [61] reveals a striking signature of metabolic similarity. We have analyzed recent aging metabolomics literatures ( Fig.…”
Section: Metabolomics Studies Of Experimental Sleep Deprivationmentioning
confidence: 99%
“…In addition, histidine and tryptophan were also found to be significantly changing with age [47]. The same cohort samples were used to demonstrate metabolic association of leucocyte telomere length (LTL), a key cellular phenotype of aging [48]. Specifically, 2 lysolipids, 1-stearoylglycerophosphpinositol and 1-palmitoylglycerophosphoinositol were found to be negatively associated to LTL along with two ␥glutamylamino acids (Supplementary information S1) [48].…”
Section: Aging Metabolomics Studies In Humans and Non-human Primatesmentioning
confidence: 99%
See 1 more Smart Citation